Aryne-Based Multicomponent Coupling Reactions - Ghorai, Sourav; Lee, Daesung (Synlett, 2020)
Multicomponent reactions (MCRs) constitute a powerful synthetic tool to generate a large number of small molecules with high atom economy, which thus can efficiently expand the chemical space with molecular diversity and complexity. Aryne-based MCRs offer versatile possibilities to construct functionalized arenes and benzo-fused heterocycles. Because of their electrophilic nature, arynes couple with a broad range of nucleophiles. Thus, a variety of aryne-based MCRs have been developed, the representative of which are summarized in this account.1 Introduction2 Aryne-Based Multicomponent Reactions2.1 Trapping with Isocyanides2.2 Trapping with Imines2.3 Trapping with Amines2.4 Insertion into π-Bonds2.5 Trapping with Ethers and Thioethers2.6 Trapping with Carbanions2.7 Transition-Metal-Catalyzed Approaches3 Strategies Based on Hexadehydro Diels–Alder Reaction3.1 Dihalogenation3.2 Halohydroxylation and Haloacylation3.3 Amides and Imides3.4 Quinazolines3.5 Benzocyclobutene-1,2-diimines and 3H-Indole-3-imines3.6 Other MCRs of Arynes and Isocyanides4 Conclusion
Keywords: arynes; multicomponent reactions; Diels–Alder reaction; silver; heterocycles